The NICE Guideline On Medicinal Cannabis: Keeping Pandora's Box Shut Tight?. (4th February 2020) - Case, Paula
Abstract: November 2018 saw the prescription of unlicensed medicinal cannabis products being legalised in the UK, accompanied by loud media fanfare. One year on, it seems that access to medicinal cannabis in this country continues to be extremely rare, raising questions about what might be stopping doctors from making use of the legal space to prescribe. This commentary explores some of these questions, outlining the theoretical space for legal prescribing and examining whether the recently announced National Institute for Health and Care Excellence guideline does anything to ease the deadlock.